(untitled) (European Journal of Emerging Technology and Discoveries, 2024)
In this scientific article, ways to increase the economic efficiency of the use of the cluster system in increasing the export potential of the textile industry in Uzbekistan and the actual problems in the development of the textile industry have been determined, and proposals and recommendations have been developed for their elimination.